2013
DOI: 10.1177/0734904113505677
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of width effects on horizontal flame spread over extruded and expanded polystyrene foam surfaces

Abstract: In order to explore the mechanisms of horizontal flame spread over thermal insulation foam surfaces, extruded polystyrene and expanded polystyrene foams were selected to carry out a series of experiments with different sample widths ranging from 4 to 16 cm. Temperatures in both the solid phase and the gas phase were measured, with considerable differences being found between extruded polystyrene and expanded polystyrene in their temperature profiles. Extruded polystyrene also showed a distinct pyrolysis stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…This group of tests was designed to evaluate the influences of different HRRs. Moreover, the HRRs simulated in this section were selected according to combustion tests of common flammable objects that piled up in the stairwell [28][29][30][31]. Moreover, this was carried out with reference to previous studies [15][16][17][18].…”
Section: Simplified Model and Configurationsmentioning
confidence: 99%
“…This group of tests was designed to evaluate the influences of different HRRs. Moreover, the HRRs simulated in this section were selected according to combustion tests of common flammable objects that piled up in the stairwell [28][29][30][31]. Moreover, this was carried out with reference to previous studies [15][16][17][18].…”
Section: Simplified Model and Configurationsmentioning
confidence: 99%
“…As the thermal insulation materials in this test, extruded polystyrene (XPS), which is applied in most building structures owing to its excellent constructability and economic efficiency, and flame-retardant expanded polystyrene foam (EPSFs), which is a representative material with semi-incombustible performance [29,30], were used. XPS is produced through extrusion molding by adding a hydrocarbon foaming agent to a polystyrene resin [1,2,[31][32][33]. It has been used in buildings in South Korea where large-scale fires have occurred, and the cause of the fire spread was found to be the thermal insulation materials [2,31,32].…”
Section: Test Materialsmentioning
confidence: 99%
“…It was found that the heat transfer mechanism had changed with different sample widths: the flame spread was controlled by convection transfer regime initially while gradually changed to radiation regime as the sample width increased. Huang et al (2011Huang et al ( , 2012 and Jiang et al (2013Jiang et al ( , 2014 investigated the different combustion behaviors of XPS and expanded polystyrene (EPS). Qualitative observations of some thermal properties with some theoretical analysis were provided.…”
Section: Introductionmentioning
confidence: 99%